EDM performance characteristics and electrochemical corrosion analysis of Co-Cr alloy and duplex stainless steel: A comparative study. (August 2021) - Mahajan, Amit; Singh, Gurpreet; Devgan, Sandeep; Sidhu, Sarabjeet Singh
Cobalt-chromium alloy (F-90) and duplex stainless steel (DSS-2205) belong to the family of metallic biomaterials, which are frequently used for the manufacture of dental prosthetics, artificial implants including knee and hip joints. This article addresses the investigation highlights of electrical discharge machining (EDM) of Co-Cr alloy and duplex stainless steel using different electrode materials for the evaluation of optimum machining parameters. The samples with superior machining performance and surface integrity were analyzed by electrochemical corrosion testing and found that the EDM treated samples portrayed a notable improvement in the corrosion resistance compared to bare metal. Our results demonstrated that both the substrates i.e. Co-Cr alloy and DSS-2205 were dominantly affected by the intensity of the applied current, and participated in the material removal rate with a contribution of 93.81% (23.37 mm 3 /min., Co-Cr alloy) and 87.32% (39.76 mm 3 /min., DSS-2205) respectively. However, the surface roughness of the machined Co-Cr alloy (1.080 µm) was majorly influenced by the current (contribution: 67.24%) and electrode (contribution: 28.27%). Whereas, pulse-on (contribution: 58.37%) and electrode (contribution: 30.52%) were significant for the surface roughness (1.150 µm) of the machined DSS-2205. Moreover, the machined surface also demonstrates the porosity (∼3 to ∼5 µm) and formation of intermetallic oxides, carbon phases on the samples machined at a higher value of current i.e. 16 Ampere. Field emission scanning electron microscopy and X-ray diffractometer were used to scrutinize the surface topography and compositional analysis of the machined substrates. The alternation of the substrate surface observed helpful in enhancing the corrosion resistance of Co-Cr alloy and duplex stainless steel by 80.88% (corrosion rate: 0.00029 mm/year) and 96% (corrosion rate: 0.00763 mm/year), comparative to their respective untreated samples.